CPE in Beaumont Hospital – Trying to understand an increasing and challenging pathogen. Issue 2 (28th February 2020) - Skelly, Emma; Foley, Margaret; Skally, Mairead; Reilly, Aoife; Humphreys, Hilary; Fitzpatrick, Fidelma
Abstract : Background: The prevention and control of carbapenemase-producing Enterobacteriales (CPE) cross-infection is increasingly difficult worldwide. Patients exposed to a CPE positive patient in our institution are informed, offered CPE screening and their clinical records flagged on our hospital information system since mid-2017 as recommended nationally. However, no assessment of the numbers of CPE contacts has been performed prior to this. Objective / Aims: To retrospectively identify and quantify CPE contacts patients in Beaumont Hospital between 2011 and mid-2017. Methods: Patients with an exposure to CPE positive patients while an inpatient were identified retrospectively. Each CPE contact was evaluated for: number of CPE screens taken, mortality, existing multidrug resistant colonisation, duration of CPE exposure, recurrent hospitalisation after CPE exposure and CPE colonisation within this group. Results: Twenty-eight CPE positive patients were identified from January 2011 – May 2017. This included 22 OXA-48, six KPC and four NDM patients; two patients had OXA 48 and NDM genes. A total of 237 patients were identified as CPE contacts of whom 124 (52.7%) had 190 CPE screens. Four CPE contact patients were identified as CPE positive (all OXA-48), however, only three (1.2%) were associated with exposure to one of the 28 CPE positive patients. Conclusions: The identification of potential CPE contacts and subsequent CPE positive patients is essential to prevent further cross-transmission. Of the CPE contacts screened, only three CPE positive patients were associated with exposure to the index patients, which may indicate good adherence with infection control precautions or low sensitivity of culture-based screening.